The Intergenerational Transfer of Infant Mortality in Northern Norway during the 19th and Early 20th Centuries - Hilde Leikny Sommerseth (Historical Life Course Studies)
This paper is one of a series of five studying the intergenerational transfer of infant mortality down the maternal line. All five studies share the same theoretical and methodological design, and use data derived from a standard database format: the Intermediate Data Structure (IDS). The data for the research reported in this paper were derived from a longitudinal dataset covering the 19th and 20th century population of the province of Troms in Northern Norway. Our results suggest that there was an element of intergenerational transmission in women’s risk of experiencing an infant death; the children of a woman whose mother had had a high number of infant deaths also had a greater risk of dying before their first birthday. The risk of an infant death occurring among the children of daughters from such ‘high risk’ families was at least 30 per cent higher than that amongst infants born to the daughters of mothers who had experienced zero infant deaths.